Energy budget adjustment of sea cucumber Apostichopus japonicus during breeding period. (29th January 2018) - Ru, Xiaoshang; Zhang, Libin; Liu, Shilin; Sun, Jingchun; Yang, Hongsheng
Abstract: Reproductive success is unpredictable for many cultured echinoderms. And cost of reproduction plays an important role in animal life‐history. Therefore, understanding cost of reproduction contributes to improving breeding techniques during broodstock rearing in aquaculture. In this study, energetic costs during breeding were explored in the sea cucumber, Apostichopus japonicus, an important aquaculture species in China, Japan and South Korea. The food intake, digestive functions and energy budget patterns were estimated at different breeding stages. Unexpectedly, in the growing gonad phase of the sea cucumber lifecycle, animals showed a decline in feed consumption (from 4.49 to 2.6 g ind −1  day −1 ), ingestion rate (from 0.4 to 0.13 g g −1  day −1 ) and apparent digestive rate (from 14.73% to 10.92%), resulting in a reduced energy input. In addition, the increased energy investment in reproduction (from 1.76% to 15.61%) resulted in a decrease in energy allocated to soma growth (from 17.1% to 5.64%) and self‐maintenance (from 47.82% to 34.67%). These results suggest that reproduction impairs energy acquisition ability in breeding A. japonicus . And broodstock can adapt energy shortage by internal adjustment of energy allocation strategy.